Criminal Law Enforcement of Indonesian Commerce Act Number 7 the Year 2014 for Corporation Perpetrators: Why It Will Be Difficult - Zakaria, Alfons (Brawijaya Law Journal, 2019)
Indonesian laws have recognized the legal person as a subject of criminal law. It can be seen in all regulations enacted recently acknowledging that â€œany personâ€ is a natural person (natuurlijk persoon) and legal person (rechtspersoon) who are liable for criminal punishments. Related to legal person or corporation, Indonesia, on the other hand, regulates corporate criminal responsibility differently in every single law. Some laws contain complete provisions, but others may fail to set the regulation properly. The Indonesian Commerce Act Number 7 the year 2014, for example, the legislators might miss drawing the provisions regulating corporate criminal responsibility. The Act recognizes corporations as a legal subject, but there is the absence of provisions related to when corporations shall be categorized committing a crime, which party shall be responsible when corporations shall be responsible, and what punishments shall be proper for corporations. Furthermore, it is commonly used, that if there is an absence of criminal law provisions in an act, the Criminal Code and Criminal Procedure Code will be the referral sources. In terms of corporate criminal responsibility regulation, however, both the Criminal Code and Criminal Procedure Code do not recognize the corporation as the subject of criminal law. Thus, the codes may not suitable as the referral sources for corporate crime law. Unfortunately, corporations violating the Act, then, will be difficult to be enforced in the judicial process. As a legal research paper, it will argue that the absence of the provision related to corporate criminal responsibility leads to the failure of law enforcement of corporation wrongdoings by presenting prospective consequences of the absence of such provisions.